Literature Study: Babesiosis in Dogs in The Period of 2013-2023 - Aina Dzatun Nithaquin; Dodik Prasetyo; Tiara Widyaputri; Aldila Noviatri (Journal of Applied Veterinary Science And Technology, 2024)
Background: Babesiosis is an infectious disease caused by Babesia spp. with tick vectors Rhipicephalus sanguineus and Dermacentor margniatus (a tick-borne disease). Babesiosis transmission occurs through tick bites or blood transfusions. Diagnostic techniques involve the microscopic examination of blood smears, hematology, blood chemistry, and PCR laboratory analysis. Purpose: To determine the clinical symptoms, confirmation of diagnosis, and therapy used for babesiosis conditions in dogs. Method: Analysis was conducted on 22 literature cases of babesiosis in dogs with a publication period of 2013-2023. The analysis was carried out using the descriptive analysis method, a problem-solving procedure that describes the condition of the subject or object based on facts, characteristics, and any relationships between the phenomena being investigated. Qualitative research methods were used to examine natural object conditions, as a key instrument. Data source sampling was done purposively, the data collection techniques were combined, the data analysis was either inductive or qualitative, and qualitative research results emphasize meaning. Result:  Dog patients with babesiosis have the highest prevalence of clinical symptoms, namely anorexia (62.5%), vomiting (33.3%), pyrexia (54.16%) lethargy (45.83%), brownish urination (29.16%), and ectoparasite infestation (29.16%). Confirmation of the diagnosis carried out included the microscopic examination of blood smears (100%), hematology (91.66%), blood chemistry (41.66%), and Polymerase Chain Reaction (PCR) (20.83%). The therapeutic management used included 3 combinations of antibiotics in 7 cases (31.81%), combination therapy of 2 antibiotics and an antiparasitic in 3 cases (13.63%), and combination therapy of 1 antibiotic and antiparasitic in 3 cases (13.63%).  Conclusion:  Antiparasitic therapy that can be used is imidocarb dipropionate, which works by inhibiting inositol in the erythrocytes infected with Babesia spp. and diminazene aceturate, which works by disrupting parasite DNA synthesis.